A wireless reflectance pulse oximeter with digital baseline control for unfiltered photoplethysmograms - Li, Kejia; Warren, Steven (My University, 2011)
Pulse oximeters are central to the move toward wearable health monitoring devices and medical electronics either hosted by, e.g., smart phones or physically embedded in their design. This paper presents a small, low-cost pulse oximeter design appropriate for wearable and surface-based applications that also produces quality, unfiltered photo-plethysmograms (PPGs) ideal for emerging diagnostic algorithms. The design's “filter-free” embodiment, which employs only digital baseline subtraction as a signal compensation mechanism, distinguishes it from conventional pulse oximeters that incorporate filters for signal extraction and noise reduction. This results in high-fidelity PPGs with thousands of peak-to-peak digitization levels that are sampled at 240 Hz to avoid noise aliasing. Electronic feedback controls make these PPGs more resilient in the face of environmental changes (e.g., the device can operate in full room light), and data stream in real time across either a ZigBee wireless link or a wired USB connection to a host. On-board flash memory is available for store-and-forward applications. This sensor has demonstrated an ability to gather high-integrity data at fingertip, wrist, earlobe, palm, and temple locations from a group of 48 subjects (20 to 64 years old).
Keywords: Filter-free; High-fidelity photoplethysmogram; Low cost; Pulse oximeter; Reflectance sensor; Surface biosensor; Wearable; Wireless